Enhancement of Student’s Critical Thinking Skill through Science Context-based Inquiry Learning (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aims to enhance critical thinking skill through science context-based inquiry learning (SCOIL). This study is a quasi-experimental research with pretest and posttest control group design. The SCOIL was carried out in seventh-grade junior high school in Bogor with 56 students consisted of 24 boys and 36 girls. Data were collected by giving out critical thinking skill tests, observing the teaching and learning process, and students’ activities. Those data were analyzed descriptively and inferentially. Syntax of SCOIL was namely observation, investigation, representation, conclusions, and communication. The result of the SCOIL model implementation showed increased activity with high category and N-gain critical thinking skill was categorized at the medium level. The significance test showed the critical thinking skills of students with the SCOIL model are greater than the guided inquiry learning model. It can be concluded that the SCOIL model can enhance the critical thinking skills of junior high school students.